Synthesis and Crystal Structure of Di(thiocyanato-κN)bis(1,10-phenanthroline-5,6-dione-κ2N,N´)- Manganese(II): [(C12H6N2O2)2Mn(NCS)2]2 - DONG, HUA-ZE; LI, MENG; LI, BAI-ZHONG (Asian Journal of Chemistry, 2010)
A novel 3D supramolecular complex di(thiocyanato-kN)bis(1,10- phenanthroline-5,6-dione-k2N,N')manganese(II) with molecular formula [(C12H6N2O2)2Mn(NCS)2]2, was formed by the reaction of 1,10-phenanthroline- 5,6-dione with Mn(NCS)2, in which metal ion was in a sixcoordinated environments with a distorted octahedral geometry. Then independent mononuclear units are linked each other and pack in 3Dsuperamolecular network via hydrogen bonds interactions. The crystal is monoclinic, space group C2/c with unit cell parameters: a = 33.371 (3) Å, b = 8.8648 (8) Å, c = 18.7352 (18) Å, a = 90º, b = 116.137 (1)º, g = 90º, V = 4975.6 (8) Å3, Z = 4, Mr = 1182.95, Dc = 1.579 g/cm3, μ = 0.746 mm-1, F(000) = 2392, R = 0.0431, wR = 0.1085 for 4363 reflections with I > 2s(I).